2009
DOI: 10.1017/s0030605309990275
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes, not implementation, predict conservation success

Abstract: To use more effectively the limited resources available for conservation there is an urgent need to identify which conservation approaches are most likely to succeed. However, measuring conservation success is often difficult, as it is achieved outside the project time frame. Measures of implementation are often reported to donors to demonstrate achievement but it is unclear whether they really predict conservation success. We applied a conceptual framework and scorecard developed by the Cambridge Conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 14 publications
1
65
0
3
Order By: Relevance
“…et al, 2007). The unexpected outcomes between fox presence and malleefowl outcomes reinforce the importance of analysing and synthesizing existing data on changes in population or abundance for the threatened species or ecosystem of interest, rather than measuring the level of threat reduction achieved or actions implemented, assuming follow-on conservation benefits (Kapos et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2007). The unexpected outcomes between fox presence and malleefowl outcomes reinforce the importance of analysing and synthesizing existing data on changes in population or abundance for the threatened species or ecosystem of interest, rather than measuring the level of threat reduction achieved or actions implemented, assuming follow-on conservation benefits (Kapos et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of clear and measurable objectives, it is impossible to evaluate the degree to which this is achieved. Indeed, some studies have suggested that the setting of clear programme outcomes is a better indicator of the likelihood of the project's success than the degree to which its planned activities are implemented (Forgie et al 2001;Kapos et al 2009;Biddle & Koontz 2014). Although this issue has been reported in reviews of community-led conservation initiatives (e.g.…”
Section: Evaluating Success and Performance Of Projectsmentioning
confidence: 81%
“…However, a number of authors have cautioned against the use of outputs as indicators of a project's success unless there are robust causative mechanisms linking those outputs to desired outcomes (Tear et al 2005;Ferraro & Pattanayak 2006;Thomas & Koontz 2011). A general focus on outputs without evidence of these links assumes that output production will lead to positive environmental change, yet the degree of implementation of project actions can be a poor indicator of success (Kapos et al 2009). Where conservation is output-driven, there can be significant declines in levels of environmental protection compared with programmes where outcome-driven performance targets are used (Svancara et al 2005).…”
Section: Specifying Outcomes Vs Outputsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decision makers in conservation and restoration are often faced with the challenge of having to choose the right intervention to implement from among a suite of options; the right intervention being one where the decision maker has a high degree of certainty of its effectiveness. Effective conservation and restoration require knowledge of the effectiveness and impacts of specific actions, often based on evidence of how successful a given action has been in achieving objectives previously [4]. Widespread recognition of this need has resulted in a shift from experience-based approaches [5,6] with evidence-based practice emerging as a popular approach in the fields of conservation and restoration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%